The Influence of Perceived Price and Product Quality on Shopping Decisions on the Cumart Digital Application with Customer Trust as a Moderating Variable - Rezky Agung Setiawan; Koerniawan Hidajat (Ilomata International Journal of Management, 2022)
Research on E-commerce-based product trading companies, namely the digital application Cumart, aims to determine the effect of price perception and product quality on Dutch decisions with customer trust as a moderating variable. This type of research is quantitative research and uses accidental sampling technique for sampling. The population in this study are people in the northern DKI Jakarta area. The sample in this study used the Hair et al sample formula and based on the formula it was known that the size or number of samples was 120 respondents. Questionnaire distribution using Google forms and data processing using Smart PLS.